Administración y Comunicación: En busca de un quehacer más humano (2004)
This work is needed for the relation which should exist between Administration and Communication like two proper things to do in the human condition. Plan the question about what is the human should be the iniciation for administrators and communicators in the field of the organization. However, both disciplines don’t know the conception which doean’t have a reason, which privileges administration and communication from things, without including the people which use Instruments to achieve something determined. From this optic, the man is at the same time half and final.Polars like subjetive-objetive, science-spiritual, reason-emotional, culture-nature, interior-exterior, mith-reality with each respective scale of grays, like the interaction they do, should coexist in the definition and the comprehension of the multidimensional man.The search of a human that makes is the idea inspired by this project, results to be pertinent in the occidental truth is prefered the answers, the recipes and the saving formulas, beside the answers about the same how to do from this structure is not escape the administrators and communicators cannot escape from the organization.Beside the respect for the people, it is only the respect to their identity -the human condition and the singularthe Administration and the Communication of today should propuse the respect of nature, towards the human beings that coexist of the planet. The discovery of the human genome said that the human beings are not superior from the rest of the species of nature, they are only different.